The Influence of Work Environment, Work Discipline, and Work Motivation on Employee Performance at the Salt Production Area in Sumenep, PT. Garam - Yanti, Dewi; Hidayat, Rachmad; Rahayu, Sri (Majapahit Journal of Islamic Finance and Management, 2025)
One important factor in an organization is human resources. These human resources can activate and move all components in the organization. Without people, organizations will not be able to operate and run. This study aims to examine the influence of the work environment on employee performance at the salt production area in Sumenep, PT. Garam, as well as to assess the effect of work discipline and work motivation on employee performance in the same location. In addition, the study aims to examine the joint influence of the work environment, work discipline, and work motivation on employee performance at the Pegaraman Area Sumenep PT Salt. A quantitative research approach was employed, with data collected through observation and a questionnaire. The study population consisted of all employees working in the Pegaraman Area Sumenep PT Salt. The data were analyzed using multiple linear regression analysis, hypothesis testing, and the determination coefficient analysis. The results indicate that the work environment, work discipline, and work motivation each have a partial influence on employee performance.